Odor Identification by Parkinson's Disease Patients Tested by Using Sniffin' Sticks versus Natural Spices. (28th April 2022) - Baert, Florence; Vlaemynck, Geertrui; Maselyne, Jarissa; Matthys, Christophe
Abstract : Introduction . Hyposmia is a frequent symptom of Parkinson's disease (PD), which greatly impacts patients' flavor perception and their quality of life. However, PD patients recognize some odors better than others. Identifying which food odors are still recognized by PD patients may be useful for flavor enhancement. Our aim was to evaluate the olfactory identification of Sniffin' Sticks and spice odorants in PD patients and healthy controls (HC), to identify the impact of synthetic odorants compared with real-life food and the impact of odor familiarity and pleasantness on odorant identification in PD patients. Methods . Sniffin' Sticks odorant identification was evaluated in 80 PD patients and 105 age-matched HC. In a subset, the spice odorant identification was evaluated. Results . The mean total score was higher for the Sniffin' Sticks than for the spice odor identification test in all participants (55.4% versus 22.5%). Sniffin' Sticks orange, peppermint, rose, and fish odorants were best correctly identified by PD patients, by 62.5, 53.8, 52.9, and 57.5%, respectively. Of the spice odor identification test, garlic and "no stimulus" were best correctly identified by PD patients, by, respectively, 38.2 and 67.6%. HC identified most Sniffin' Sticks odorants and spices better than PD patients. Odorant familiarity determined real-life food odorant identification. Conclusion . This study demonstrates that some food odorants, both the commercial Sniffin' Sticks as natural odorants, are still recognized by PD patients. Sniffin' Sticks were better recognized compared with real-life odorants, by both HC and PD patients. Odorant familiarity determined PD patients' odorant identification; therefore, familiar food odorants may have potential for a future flavor enhancement. Implications . This is the first study, to our knowledge, to evaluate real-life food odor identification in PD patients. Our results provide a first step towards patient-appropriate flavor enhancement strategies in PD.